Contraceptive use among pregnant women with heart disease managed in tertiary care setting - Senanayake, S.J.; Jayawardane, D.B.I.A.; Gunasekara, M.Y.; Liyanapatabandi, D.; Wijeyaratne, C.N.; Randeniya, C. (The Sri Lanka College of Obstetricians and Gynaecologists, 2006)
OBJECTIVES: To describe characteristics of women with heart disease attending a high risk antenatal clinic, to determine pre-conception planning of current pregnancy and describe their family planning practices and reasons for failure. METHOD: A cross sectional descriptive study using a pre-tested interviewer administered questionnaire. Consecutive subjects with disease, attending a combined medical-obstetric clinic from 01.03.2006 to 30.06.2006, were invited to participate. RESULTS: 60 were interviewed with a mean age of 28 ñ 5.6 years, with 18(30 percent) primigravida and 28(46.7 percent) mulrigravid. Cardiac defects were congenital in 29(48.3 percent) and acquired 31 (51.7 percent) with all of latter being of rheumatic aetiology. The interval from diagnosis of heart disease to current pregnancy ranged from 1- 28 years. Those with symptoms of New York Heart Association (NYHA) grades 1, 2 and 3 were 50 percent, 46.7 percent and 3.3 percent respectively 13(21.67 percent) women with NYHA grade 2 had one or more living children. Only 25 (41.7 percent) of the mothers had received pro pregnancy medical counselling and 5(20 percent) had conceived contrary to medical advice given to avoid a pregnancy. In the entire cohort, contraceptive practices were oral contraceptive pills (18 percent), condoms (23 percent), Depot medroxy-progesterone acetate (20 percent), while 33 percent used no contraceptive method. Of the women who had not received pre pregnancy counselling, 13 (37.1 percent) pregnancies were due to family planning failure and of them 11 (84.6 percent) were due to user failure. The source of contraceptive advice were from Obstetrician (30 percent), Midwife (26.7 percent) and Cardiologist/Physician (18.3 percent), while 15 percent had not received any advice regarding contraception. CONCLUSIONS: A significant number women with heart disease, managed in tertiary care setting, have unplanned or poorly planned pregnancies. RECOMMENDATION: Women with heart disease complicating pregnancy require a multidisciplinary approach to pregnancy planning with provision of appropriate family planning.
Keywords: CONTRACEPTIVE; TERTIARY CARE